Speculative reworkings of the good life at the end times: : Care, resilience, and relational futures in Cherie Dimaline and Rebecca Campbell - Fraile-Marcos, Ana Mª (International Journal of English Studies, 2025)
Taking as a starting point the idea that literature can function as an epistemological medium in its capacity as a testing ground where experiments in the good life can be imagined, aesthetically realized, and critically interrogated, this article turns to speculative fiction as a genre suitable for the exploration of cognitive frameworks that may lead to hopeful futurities amidst the ground-shifting transformations of the Anthropocene, supporting not only the continuity of life, but also the good life. It examines the representation of the ethics of care at the Anthropocene’s tipping point in recent speculative fiction from Turtle Island/Canada, namely, Métis Cherie Dimaline’s young adult novel The marrow thieves (2017) and its sequel, Hunting by stars (2021), and settler Canadian Rebecca Campbell’s short story cycle, Arboreality (2022). It argues that they critique the modernist nature/culture divide underpinning the disasters of the Anthropocene while reworking the notion of the good life from alternative Indigenous and new materialist relational approaches.